ANALISIS FAKTOR PENYEBAB KESULITAN MEMBACA DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS IV SD NEGERI KLAMPOK 05 - Agustin, Erin Rosna; Farhan Saefudin wahidi; Novi Yulianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the factors causing reading difficulties in Indonesian language learning among fourth-grade students at SD Negeri Klampok 05 and to describe the reading instruction strategies implemented by teachers to address these difficulties. The research employed a qualitative approach with a descriptive case study design. Data were collected through classroom observations, in-depth interviews with teachers and students, and documentation. Data validity was ensured through source and technique triangulation, while data analysis followed the interactive model of Miles, Huberman, and Saldana, including data reduction, data display, and conclusion drawing and verification. The findings revealed that students’ reading difficulties were influenced by both internal and external factors. Internal factors included limited letter recognition skills, weak memory of letter symbols, low learning motivation, and poor reading comprehension. External factors consisted of insufficient family support, lack of reading habits at home, and differences in students’ reading abilities that challenged the learning process. To overcome these problems, teachers implemented several strategies, including repeated reading exercises, collaboration with parents in supporting reading practice at home, individual reading activities, and simple dictation exercises. These strategies contributed to improving reading fluency, reading comprehension, and students’ learning motivation. The study concludes that overcoming reading difficulties requires collaboration among schools, teachers, and families to support the optimal development of students’ literacy skills.